CREATION OF AN ACTIVE ELEMENT OF A NEW BRANCH OF KNOWLEDGE ECONOMY – THE DIGITAL ECONOMY - V. L. Souponitsky; M. I. Kuternin; Ya. D. Vishnyakov (Вестник университета)
The brief analysis of the development of L. V. Kantorovich's ideas in the works of his students and followers has been presented. This intellectual base can be used in solving the problems of digital transformation, digitalization, creation of digital platforms and their ecosystems in the digital economy. It has been proposed to create an active element of a new branch of knowledge economy – the digital economy – in the form of “Association of departments of applied mathematics of economic and managerial profiles of Russian Universities”, the advisability of this decision has been substantiated. The Association will allow you to simultaneously conduct research on a wide range of topical issues of the digital economy, optimally form creative teams and expert groups, carry out constant scientific communication in real time, and connect talented young people to research between the postgraduate students, graduate students, and students. Working together in the structure of the Association, the departments of higher education institutions will be able to show the effect of synergy and achieve much more results in their activities. The Association has a great educational potential, which can be effectively used to improve the various levels of personnel potential of management systems. Creating associations in the field of breakthrough technologies is the best way to activate Russia's intellectual potential.